Microscale tribological behavior and in vitro biocompatibility of graphene nanoplatelet reinforced alumina. (August 2016) - Nieto, Andy; Zhao, Jing Ming; Han, Young-Hwan; Hwang, Kyu Hong; Schoenung, Julie M.
Abstract: Graphene nanoplatelets were added as reinforcement to alumina ceramics in order to enhance microscale tribological behavior, which would be beneficial for ceramic-on-ceramic hip implant applications. The reduction in microscale wear is critical to hip implant applications where small amounts of wear debris can be detrimental to patients and to implant performance. The addition of the GNPs lead to improvements in fracture toughness and wear (scratch) resistance of 21% and 39%, respectively. The improved wear resistance was attributed to GNP-induced toughening, which generates fine (~100 nm) microcracks on the scratch surface. In addition, active participation of GNPs was observed in the scratch subsurface of GNP-reinforced samples through focused ion beam sectioning. Friction coefficients are not significantly influenced by the addition of GNPs, and hence GNPs do not act as solid state lubricants. In vitro biocompatibility with human osteoblasts was assessed to evaluate any possible cytotoxic effects induced by GNPs. Osteoblast cells were observed to survive and proliferate robustly in the GNP-reinforced samples, particularly those with high (10–15 vol%) GNP content. Graphical Abstract: Highlights: Addition of 5 vol% GNP leads to a 39% enhancement in microscale wear resistance. It is shown that GNPs provide no intrinsic lubrication to the alumina matrix. GNP toughening by GNP pull-out and formation of fine (~100 nm) micro-cracking. GNPs inhibit sub-surface damage through energy dissipating mechanisms. Addition of GNPs has no cytotoxic effects on the proliferation of osteoblast cells.